2012
DOI: 10.1017/s0022215111003483
|View full text |Cite
|
Sign up to set email alerts
|

Cholesteatoma surgery in children: 10-year retrospective review

Abstract: Children tend to present with aggressive disease. Disease extent and ossicular chain involvement are associated with a higher risk of recurrent disease. Spontaneous improvement in hearing thresholds following cholesteatoma surgery should alert the clinician to recurrent disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…We found significant differences between childhood cholesteatoma and adult disease, the former of which was more extensive and destructive at the time of surgery. These results support the findings of other studies that have suggested cholesteatoma in children to be more aggressive 16 , 20 , 21 . Although many studies have reviewed children and adult populations with cholesteatoma, a limited number of studies have directly compared these two groups.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We found significant differences between childhood cholesteatoma and adult disease, the former of which was more extensive and destructive at the time of surgery. These results support the findings of other studies that have suggested cholesteatoma in children to be more aggressive 16 , 20 , 21 . Although many studies have reviewed children and adult populations with cholesteatoma, a limited number of studies have directly compared these two groups.…”
Section: Discussionsupporting
confidence: 89%
“…These results support the findings of other studies that have suggested cholesteatoma in children to be more aggressive. 16,20,21 Although many studies have reviewed children and adult populations with cholesteatoma, a limited number of studies have directly compared these two groups. An Egyptian study by Elrashidi 22 divided 81 patients with cholesteatoma into age-based groups: children, adolescents and adults.…”
Section: Discussionmentioning
confidence: 99%
“…It is essential to clarify that the operation technique is not the only factor influencing the risk of cholesteatoma recidivism. In addition, this risk is affected by the extent of the disease (especially mastoid extension), ossicular chain disruption, cholesteatoma location and preoperative ear discharge . However, it should be emphasized that all studies investigating the aforementioned risk factors included only children or studied a population consisting of both children and adults .…”
Section: Discussionmentioning
confidence: 99%
“…The absence of postoperative hearing improvement in adolescents, and particularly in children, contrary to obvious improvement in adults reflects the persistent adverse activity of upper respiratory tract infections. So, experience can not lead to retaining of audiological results of cholesteatoma surgery in children [10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%